Organisational Communication Patterns in Increasing Solidarity Between Members : Pola Komunikasi Organisasi Dalam Meningkatkan Solidaritas Antar Anggota - M.Rusman Hadi; Siti Zidni Ilman (Institute of Educational, Research, and Community Service, 2023)
This research aims to find and find out the communication patterns used by the HlMMAH NWDI organization Yogyakarta Special Area in enhancing and maintaining solidarity between members. The research method used in this research is the type of qualitative descriptive research, the informant's determination technique in this research uses purposeful and also the Snowball technique with data collection through interviews, direct observation, and documentation, then data analysis at a stage that begins with data reduction, data learning, and conclusion drawing, And data teaching in this study is provided in descriptive or narrative form. Based on the findings, the communication patterns used by HIMMAH NWDI DIY consist of two types: wheel structure patterns and the structural patterns of all channels or stars. Wheel-structured communication patterns are used at both formal and structural activities while all channels or stars are structured at informal activities. Solidarity is shown by making every approach to each other family-based members that are needed, helping each other members, and appreciating each other's differences